TEACHERS’ PERSPECTIVE ON USING MULTIMEDIA TECHNOLOGY FOR TEACHING ENGLISH - Izlin, Rosita; Widiyati, Elok (Sanata Dharma University Yogyakarta, 2023)
The rapid development of information and communication technology in this recent times has influenced the way the English language should be taught. This study aims to find out the use of multimedia as a technological device in English learning from the perspective of the teacher. This study involved 2 participants: the two 12th-grade English teachers of SMAN 2 Semarang. This study applied a qualitative approach with a phenomenological approach. Data were collected through observation and in-depth interviews based on three categories; kinds of multimedia, advantages, and disadvantages, and how the teacher uses the media. A thematic analysis design is used in this study. This started at the data collecting phase and lasts through the transcription, reading and re-reading, analysis, and interpretation stages of the data. It is concluded that the teachers have a positive perspective toward using multimedia technology in the classroom to teach English. The use of multimedia technology has had a major impact on the advancement of education, especially English learning.